A Study on the Chromosomes of White-cheeked Gibbon, Nomascus leucogenys (Primate, Hylobatidae) by Conventional Staining Technique - Kaewsri, Sarawut; Tanomtong, Alongklod; Supanuam, Praween; Khunsook, Sumpars; Sanoamuang, La-orsri (KKU Science Journal, 2013)
Standardized karyotype and idiogram of white-cheeked gibbon (Nomascus leucogenys) at Nakhonratchasima Zoo, was study. Blood sample were taken from 1 female and 2 males gibbons. After standard whole blood lymphocyte culture at 37 oC for 72 hr. in the presence of colchicine, the metaphase spreads were performed on microscopic slides and air-dried. Conventional staining technique was applied to stain the chromosomes. The results show that diploid chromosome number is 2n = 52, and the fundamental number (NF) is 104 in both female and male. The autosomes consist of 22 large metacentric, 8 large submetacentric, 10 medium metacentric, 4 medium submetacentric and 6 small acrocentric chromosomes. The X-chromosome is the large acrocentric and the Y-chromosome is the smallest submetacentric chromosome. The karyotype formula for the white-cheeked gibbon is as follows: 2n (52) = Lm22 Lsm8 + Mm10 + Msm4 + Sa6 + sex-chromosomes